Penegakan Hukum Administrasi Terhadap Kebakaran Hutan - Rahadina, Virda Ayu; Ratna, Edith (JURNAL USM LAW REVIEW, 2025)
This research aims to determine the enforcement of forestry law in the administrative aspect in Indonesia and the role of the Ministry of Environment and Forestry in addressing the issue of forest and land fires in Indonesia which have an impact on environmental destruction because land is cleared, that forest fires will cause pollution and forest damage. The challenges and obstacles in carrying out supervision and enforcement that arise are funding and human resource factors, lack of public awareness, and how law enforcement officers act. Earth water and all natural resources are the pillars of the economy in Indonesia with an understanding of togetherness and family where according to Article 33 paragraph (3) control is held by the state for the prosperity of society, not individuals. This research uses a normative juridical approach, examining the applicable laws and regulations as well as their implementation in society through a descriptive-analytical presentation and data collection. Forestry Law No. 41/1999 and Law No. 39/2014 is a forest empowerment regulation in Indonesia to protect the plantation sector. In this case, the Ministry of Environment and Forestry filed a lawsuit for compensation and took action against the perpetrators of forest fires and environmental degradation with administrative fines against PT RKA and PT ABS. Provisions in the regulations limit forest use which leads to forest destruction by corporations with the application of criminal sanctions for violators as a measure for law enforcement and forest conservation in the future. The novelty of this research is that it discusses the administrative law side. Penelitian ini bertujuan mengetahui penegakan hukum kehutanan dalam aspek administrasi di Indonesia dan peran KLHK dalam menyikapi persoalan kebakaran kawasan hutan dan lahan tanah di Indonesia yang berdampak pada peluluhlantahan lingkungan hidup dengan alasan pembukaan area lahan, bahwa kebakaran hutan akan menimbulkan pencemaran serta kerusakan hutan. Tantangan dan hambatan dalam menjalankan pengawasan dan penegakan yang muncul ada pada faktor dana maupun SDM, kurangnya kepedulian masyarakat serta bagaimana aparat penegak hukum dalam bertindak. Bumi dan air serta seluruh kekayaan alam sebagai tonggak perekonomian di Indonesia dengan paham kebersamaan dan kekeluarga dimana menurut Pasal 33 ayat (3) penguasaannya dipegang oleh negara guna kemakmuran masyarakat, bukan perseorangan. Penelitian ini menggunakan pendekatan yuridis normative, mengkaji ketentuan dan peraturan yang berlaku serta penerapannya di masyarakat dengan bentuk sajian deskriptif analitis serta menggunakan pengumpulan data. UU Kehutanan No. 41/1999 dan UU No. 39/2014 adalah regulasi pemberdayaan hutan di Indonesia untuk melindungi sektor perkebunan. KLHK pada kasus ini mengajukan gugatan ganti rugi dan menindak pelaku kebakaran hutan serta degradasi lingkungan dengan sanksi denda administratif terhadap PT RKA dan PT ABS. Ketentuan dalam regulasi pembatasan pemanfaatan hutan yg mengarah pada kerusakan hutan oleh korporasi dengan penerapan sanksi pidana bagi pelanggar sebagai langkah penegakan hukum dan pelestarian hutan di masa depan. Kebaruan dalam penelitian ini adalah membahas terkait sisi hukum administrasinya.